Clinical Performance Measures for Stroke Rehabilitation: Performance Measures From the American Heart Association/American Stroke Association. Issue 10 (5th August 2021) - Stein, Joel; Katz, Douglas I.; Black Schaffer, Randie M.; Cramer, Steven C.; Deutsch, Anne F.; Harvey, Richard L.; Lang, Catherine E.; Ottenbacher, Kenneth J.; Prvu-Bettger, Janet; Roth, Elliot J.; Tirschwell, David L.; Wittenberg, George F.; et al.
Abstract : The American Heart Association/American Stroke Association released the adult stroke rehabilitation and recovery guidelines in 2016. A working group of stroke rehabilitation experts reviewed these guidelines and identified a subset of recommendations that were deemed suitable for creating performance measures. These 13 performance measures are reported here and contain inclusion and exclusion criteria to allow calculation of rates of compliance in a variety of settings ranging from acute hospital care to postacute care and care in the home and outpatient setting.